Tinjauan Hukum Islam Terhadap Transaksi Kerjasama Program Afiliasi Pada Platform E-Commerce Shopee - Azizah, Azizah; Sirri, Rima Alifa; Anggraini, Silvia (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2025)
Marketing that was previously carried out traditionally has undergone changes with online marketing or through digital technology. In dealing with this shift, the marketing strategy has shifted from offline to online. One of the popular digital marketing strategies is affiliate marketing. In Indonesia, many affiliate practices are carried out by online marketplaces, for example Shopee. However, in the face of developments and variations in modern transactions, Islamic values ​​must be maintained so that they are applied. Therefore, it is necessary to examine affiliate marketing practices from the perspective of Islamic law. In this study the authors conducted legal research in the form of normative juridical research. The data analysis method was carried out qualitatively. This study aims to identify whether affiliate practices in the Shopee e-commerce platform are in accordance with the principles of Islamic economic law, such as samsarah and wakalah bil ujrah contracts. By conducting an Islamic legal review of affiliated transactions at Shopee, this study seeks to assess the legitimacy and suitability of affiliated cooperation practices with Islamic sharia values ​​and provisions. The results of this study indicate that the practice of affiliate marketing collaboration carried out by Shopee with affiliated participants can be permitted by complying with several conditions in the principles of Islamic law. The practice of paying commissions by Shopee to affiliated participants in Islam is in line with the samsarah and wakalah bil ujrah contracts